2015
DOI: 10.1063/1.4913608
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of electrical conductivity of a liquid crystal-gold nanoparticle composite by a gel network of aerosil particles

Abstract: We report electrical conductivity measurements on a pure nematic liquid crystal (LC) and its composites comprising Gold nanoparticles (GNPs) as well as aerosil particles. The inclusion of aerosil particles creating a gel network, albeit being non-conducting, surprisingly enhances the already high conductivity of the LC-GNP material. The presence of aerosil also makes the frequency dependence of the conductivity compatible with the universal phenomenon expected for disordered solids despite the LC confined in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Recalling that the efficiency of the LEDs is lower in the green/yellow spectral range, the system investigated here may be attractive. Nano‐soft composites comprising LCs as host and nanostructures as the guest is an emerging area of research that gets benefitted by the unique characters of the latter in the self‐assembling features of LCs . A variety of nanoparticles have been employed to alter/tune the LC properties.…”
Section: Introductionmentioning
confidence: 99%
“…Recalling that the efficiency of the LEDs is lower in the green/yellow spectral range, the system investigated here may be attractive. Nano‐soft composites comprising LCs as host and nanostructures as the guest is an emerging area of research that gets benefitted by the unique characters of the latter in the self‐assembling features of LCs . A variety of nanoparticles have been employed to alter/tune the LC properties.…”
Section: Introductionmentioning
confidence: 99%
“…Equation (8) can also be written in the following form, considering: σ DC where σ DC represents the DC conductivity, f c stands for the characteristic frequency, and n is a parameter, which represents the degree of interaction between the mobile ions and their surroundings. The value of n is normally situated between 0 and 1, however some authors have found values where n > 1 [ 33 , 34 , 35 , 36 ]. Many other models are available to analyze the frequency dependence of the complex conductivity like Cole–Cole, Cole–Davidson, Havriliak–Negami, or Kohlrausch–Williams–Watts functions transformed beforehand into their conductivity representations [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…This increase in the conductivity is attributed to the formation of chains of gold nanoparticles [162,164]. The high electrical conductivity of nematic liquid crystal-gold nanoparticle nano-composites can be enhanced even more by mixing them with dielectric aerosil particles [165]. The formation of chains and networks of metal nanoparticles in liquid crystal nano-composites points to the involvement of the percolation processes.…”
Section: Metal Nanoparticles In Liquid Crystalsmentioning
confidence: 97%
“…Table 3 provides a short summary of their effects on the electrical properties of liquid crystals [154][155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172]. The majority of published papers report an increase in the electrical conductivity of liquid crystals doped with metal nanoparticles [156][157][158][160][161][162][163][164][165][166][167]169,171].…”
Section: Metal Nanoparticles In Liquid Crystalsmentioning
confidence: 99%